Un modèle économétrique de l’économie canadienne pendant l’entre-deux-guerres - Racette, Daniel (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractEven though the Canadian Great Depression was one of the worst in the Western World, there are no recent articles where the phenomenon is analyzed as a whole. In this paper, the Interwar business cycles are analyzed in the context of amacroeconomic model with monthly data. The model features the specification of the money supply process, of the balance of payments and of the interaction between these variables.The results of estimation of the model indicate that Canada followed the US in its depression because it adhered too closely to the rules of the GoId Standard. Canada should have depreciated its currency at least to the extent of the depreciation of the pound sterling with respect to the US dollar. The results also indicate that the Finance Act did not play the important role that was assigned to it in the literature (Courchene, 1969).